Pengaruh Downward Communication dan Kompensasi Terhadap Kepuasan Kerja Karyawan Bagian Pengembangan Outlet Kantor Pos Cabang Utama Surabaya 60000 - Galuh Noviani; Sri Umiyati; Setya Prihatiningtyas (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2022)
This study is conducted to determine (1) the effect of Downward Communication on job satisfaction of the main branch post office Surabaya 60000, (2) the effect of compensation on job satisfaction of the employees of the Surabaya main branch post office 60000, (3) the effect of Downward Communication and Compensation on job satisfaction employees of the main branch post office Surabaya 60000. The sample uses 52 employees. This research includes causal associative research using a quantitative approach, namely validity test, reliability test, classical assumption test, multiple regression, t statistic test, F statistic test, and coefficient of determination (R2).  It is proven through the F test, F count 3,18 > F table 704,470 and a significant value of 0,000 < 0,05 it can be concluded that Downward Communication (X1) and Compensation (X2) have a positive and significant effect on employee job satisfaction (Y) simultaneously and the coefficient of determination 3,4%.